Effectiveness of Case Manager Led Multi-Disciplinary Team Approach on Glycemic Control Amongst T2DM Patients in Primary Care in Riyadh: A Retrospective Follow-Up Study - Abdulmajeed Alshowair; Saleh Altamimi; Saad Alshahrani; Rehab Almubrick; Syed Ahmed; Ali Tolba; Fatimah Alkawai; Faisal Alruhaimi; Eman Alsafwani; Fatima AlSuwailem; Haiam Abdalla; Amro Abdel-Azeem (SAGE Publishing, 2023)
Objectives: Our study aims to assess the effectiveness of implementing a case manager-led Multidisciplinary Team approach in the primary healthcare setting on improving glycemic control and reducing cardiovascular risks for T2DM patients over a 6-month period. Methods: This retrospective record-based follow-up study was carried out on 3060 uncontrolled T2DM patients in primary healthcare centers in Riyadh First Health Cluster over a period of 6 months. The patient records are investigated and analyzed, including demographic characteristics and measurements of Hemoglobin A1c (HbA1c), Low-Density Lipoprotein Cholesterol (LDL-C), total cholesterol, and BP levels at enrollment and after 6 months of Multi-Disciplinary Team follow-up. The changes in the study variables and their correlations to each other are tested using Statistical Package for the Social Sciences software. Results: At enrollment, our patients were characterized by poor glycemic control (HbAIC > 8%). Most of them have high body weight with a mean BMI of (31.2 ± 1.7), and nearly two-thirds are either hypertensive or have dyslipidemia (43.4% and 47.3% respectively). After 6 months of MDT follow-up, there is a significant improvement in glycemic control among 1971 patients (64.4%), with a reduction in the mean level of different outcomes relative to baseline HbA1c (−15%, P  < .001), total cholesterol (−9.0%, P  < .001), LDL-C (−11.0%, P  < .001), systolic BP (−7.7%, P  < .001), and diastolic BP (−10.5%, P  < .001). The improved glycemic control showed a significant positive correlation with the number of MDT visits but negatively correlated with BMI and the number of comorbidities. In addition, the improvements in secondary outcomes were positively and significantly correlated with such improvements in glycemic control. Conclusion: Case-manager-led MDT approach significantly improves glycemic control and significantly improves control over dyslipidemia and hypertension, reducing cardiovascular risks, and unfavorable events among such diabetic patients. We highly recommend developing more MDTs, training case managers, and rigorously evaluating the MDT approach.